2016
DOI: 10.1128/jvi.00994-16
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Reduces Memory CD4 T-Cell Survival by Interfering with Interleukin-2 Signaling Early during HIV-1 Infection

Abstract: Early HIV-1 infection is characterized by enhanced tryptophan catabolism, which contributes to immune suppression and disease progression. However, the mechanism by which kynurenine, a tryptophan-related metabolite, induces immune suppression remains poorly understood. Herein, we show that the increased production of kynurenine correlates with defective interleukin-2 (IL-2) signaling in memory CD4 T cells from HIV-infected subjects. Defective IL-2 signaling in these subjects, which drives reduced protection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 70 publications
3
44
0
Order By: Relevance
“…Emerging data suggest that kynurenine may play a more direct role than the consumption of tryptophan catabolized by IDO in immune regulation and responses in tumor microenvironment . Kynurenine can activate transcription factor aryl hydrocarbon receptor (AhR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging data suggest that kynurenine may play a more direct role than the consumption of tryptophan catabolized by IDO in immune regulation and responses in tumor microenvironment . Kynurenine can activate transcription factor aryl hydrocarbon receptor (AhR).…”
Section: Discussionmentioning
confidence: 99%
“…32 Emerging data suggest that kynurenine may play a more direct role than the consumption of tryptophan catabolized by IDO in immune regulation and responses in tumor microenvironment. [33][34][35] Kynurenine can activate transcription factor aryl hydrocarbon receptor (AhR). The activation of AhR induces a number of immunosuppressive phenotypes including the generation of immunetolerant dendritic cells and regulatory T cells, which collectively foster a tumor immunological microenvironment that is defective in recognizing and eradicating cancer cells.…”
Section: Higher Circulating Ktr Concentrations and Risk Of Lung Cancermentioning
confidence: 99%
“…In fact, kynurenine-a metabolite of L-tryptophan-has been shown to reduce memory CD4 T cell survival. 151 Studies by our group and others have shown that Arg1-expressing tumor-associated myeloid cells exhibit suppressive activity against T cells. 152,153 Lactic acid, a by-product of tumor metabolism, has been found to suppress T cell proliferation and production of cytokines.…”
Section: Unique Aspects Of Tme Of Gbmmentioning
confidence: 97%
“…These enzymes are highly expressed by tumor cells and/or myeloid cells within the TME and can cause T cell suppression. In fact, kynurenine—a metabolite of L‐tryptophan—has been shown to reduce memory CD4 T cell survival . Studies by our group and others have shown that Arg1‐expressing tumor‐associated myeloid cells exhibit suppressive activity against T cells .…”
Section: Car T Cells and The Suppressive Microenvironment Of Brain Tumentioning
confidence: 98%
“…CD4 T-cell counts in HIV-1 positive women decrease in pregnancy before restoration post-partum, and under ART pregnancy is not associated with HIV-1 disease progression (25,26). In early HIV-1 infection IL-2 signaling is compromised which impacts the development and maintenance of Tcell memory populations, while other work suggests the degranulation capacity of CD8 cytotoxic T-cells is disrupted, and CD4 and CD8 T-cell subset frequencies are skewed even under ART (8,(27)(28)(29)(30). Memory CD4 T-cell frequency is increased in HIV-1 positive pregnant and non-pregnant women compared to their HIV-1 negative counterparts, although detailed changes in T-cell memory subsets have not been explored between nonpregnant and pregnant HIV-1 positive women under ART (31).…”
Section: Introductionmentioning
confidence: 99%